HiFENS: high-throughput FISH detection of endogenous pre-mRNA splicing isoforms. Issue 22 (16th October 2022) - Shilo, Asaf; Pegoraro, Gianluca; Misteli, Tom
Abstract: Splicing factors play an essential role in regulation of alternative pre-mRNA splicing. While much progress has been made in delineating the mechanisms of the splicing machinery, the identity of signal transduction pathways and upstream factors that regulate splicing factor activity is largely unknown. A major challenge in the discovery of upstream regulatory factors of pre-mRNA splicing is the scarcity of functional genomics screening methods to monitor splicing outcomes of endogenous genes. Here, we have developed HiFENS (hi gh throughput F ISH detection of en dogenous s plicing isoforms), a high-throughput imaging assay based on hybridization chain reaction (HCR) and used HiFENS to screen for cellular factors that regulate alternative splicing of endogenous genes. We demonstrate optimized detection with high specificity of endogenous splicing isoforms and multiplexing of probes for accurate detection of splicing outcomes with single cell resolution. As proof-of-principle, we perform an RNAi screen of 702 human kinases and identify potential candidate upstream splicing regulators of the FGFR2 gene. HiFENS should be a useful tool for the unbiased delineation of cellular pathways involved in alternative splicing regulation.